2021
DOI: 10.1111/1346-8138.15958
|View full text |Cite
|
Sign up to set email alerts
|

Clinical analysis of generalized pustular psoriasis in Chinese patients: A retrospective study of 110 patients

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
50
6
11

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(89 citation statements)
references
References 13 publications
(15 reference statements)
22
50
6
11
Order By: Relevance
“…The incidence of a family history of psoriasis ranged from 0 to 31.2% in previous reports. 12-14,17-18,21 In our study, 15.6% of patients had a family history, which is consistent with the findings of Zheng et al . 17 (14.5%).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The incidence of a family history of psoriasis ranged from 0 to 31.2% in previous reports. 12-14,17-18,21 In our study, 15.6% of patients had a family history, which is consistent with the findings of Zheng et al . 17 (14.5%).…”
Section: Discussionsupporting
confidence: 92%
“…Zheng et al . 17 included significantly more male than female patients (80/30), but the ratio was equal in the GPP −PsV group (8/8); this is consistent with our results (21/22).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Like moderate-to-severe psoriasis, GPP is associated with an increased occurrence of comorbidities compared to the general population. 4 Comorbidities that have been reported in GPP include obesity, hypertension, hyperlipidemia, diabetes, uveitis, 4–7 cholestasis, 8 joint involvement, 4–7 , 9 , 10 allergic rhinoconjunctivitis and peptic ulcer disease. 4 , 7 …”
Section: Introductionmentioning
confidence: 99%
“…GPP can be further classified as von Zumbusch‐type GPP, GPP of childhood and impetigo herpetiformis (GPP of pregnancy). Previous studies have shown that the mean age of GPP onset is around 40 years, 2,3 and onset at > 60 years of age is extremely rare 4 . For all types of psoriasis, patients with elderly‐onset GPP (onset at > 60 years) had milder disease and a lower incidence of positive family history.…”
mentioning
confidence: 99%